Climate Smart Agriculture and Gender Learning Agenda - Global Knowledge Initiative (Global Knowledge Initiative, 2022)
As inputs into the co-creation of the CGIAR GENDER Platform’s Climate Smart Agriculture and Gender Learning Agenda, GKI has conducted a literature scan to develop an Evidence Library on the topic. This will become a permanent resource hosted by the GENDER Platform. During the Learning Agenda Process, analysis of its contents will support identification of existing knowledge on the intersection of CSA and gender, and existing gaps.